A survey on dental undergraduates' knowledge of oral radiology - Sergio Lins de Azevedo-Vaz; Karla de Faria Vasconcelos; Karla Rovaris; Naiara de Paula Ferreira; Francisco Haiter Neto (Universidade Estadual de Campinas, 2015)
Dentists' incorrect behavior with regards to Oral Radiology, as reported in the literature, has been related to inadequate training of undergraduates. Aim: This study assessed dental undergraduates' knowledge of Oral Radiology. Methods: A questionnaire containing 30 questions pertaining to three domains - General Principles, Radiobiology/Radioprotection and Technique/Interpretation - was used as data collection instrument. A total of 195 students answered the questionnaires. Results: No statistically significant differences were found between second-, third- and fourthyear students (p>0.05) when the whole questionnaire and the General Principles domain (p>0.05) were considered. The Technique/Interpretation domain presented a borderline statistical significance level (p=0.051), with more correct answers attributed to second-year students. A statistically significant difference (p<0.05) was seen for the Radiobiology/Radioprotection domain, in which the fourth-year students performed better. Conclusions: Dental undergraduates' knowledge of Oral Radiology did not increase or decrease significantly comparing the undergraduate years. However, with the exception of the Technique/Interpretation domain, students of more advanced undergraduate years answered more correctly the questions. Nevertheless, the Technique/ Interpretation domain should be reinforced throughout the undergraduate course.